2005
DOI: 10.1093/toxsci/kfi100
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Toluene Exposure Alters Agonist and Antagonist Sensitivity and NR2B Subunit Expression of NMDA Receptors in Cultured Cerebellar Granule Neurons

Abstract: Toluene has been reported to antagonize the function of N-methyl-D-aspartate (NMDA) receptors. In this study, the effects of neonatal toluene exposure on NMDA receptors in primarily cultured cerebellar granule neurons were examined. Sprague-Dawley rats were treated with toluene (0, 200, 500, and 1000 mg/kg, i.p.) from postnatal day (PN) 4 to PN 7. Under toluene-free conditions, Ca2+ signals of cultured neurons in response to glutamate and NMDA were measured for up to 14 days. The expression of NMDA receptor su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Moreover, it has been reported that neonatal toluene exposure (0, 200, 500 or 1000 mg kg −1 , i.p.) on postnatal days 4–7 altered NR2B subunit expression in cultured cerebellar granule neurons (Chen et al , ). It is possible that toluene caused memory retention or recall memory deficit via the neurotoxic property of glutamate, a ligand for NMDA receptor, which increased significantly in a single acute administration in mice (Win‐Shwe et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that neonatal toluene exposure (0, 200, 500 or 1000 mg kg −1 , i.p.) on postnatal days 4–7 altered NR2B subunit expression in cultured cerebellar granule neurons (Chen et al , ). It is possible that toluene caused memory retention or recall memory deficit via the neurotoxic property of glutamate, a ligand for NMDA receptor, which increased significantly in a single acute administration in mice (Win‐Shwe et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathological effects of some abused CNS drugs (e.g., alcohol, MK-801) have been show to be dependent on the stages of development, little similar work has been done with toluene. To address this issue, Chen et al [2005] treated Sprague-Dawley rats exposed to toluene (200-1,000 mg/kg; i.p.) from PND4 -PND7 and reported that toluene exposure, along with producing lower brain weights, dose-dependently reduced intracellular Ca 2 þ signals in response to glutamate/glycine and NMDA/glycine in cultured cerebellar granule neurons.…”
Section: Pharmacodynamics/pharmacokinetics Of Toluene Teratologymentioning
confidence: 99%
“…The oxidative stress hypothesis is supported by studies showing that the administration of antioxidants such as melatonin can counter the neurotoxic effects of toluene (Baydas et al, 2003; Pascual et al, 2010). In addition, because glutamatergic NMDA receptors play an important role in neural development and plasticity (Cull‐Candy et al, 2001) and because toluene administered during the preweaning period significantly altered NMDA receptor expression and function (Chen et al, 2005; Chien et al, 2005; Lee et al, 2005), it is possible that NMDA dysfunction may significantly contribute to the structural cell impairments observed in this and previous developmental studies. Moreover, considering that GABAergic transmission is significantly altered by the inhalation of volatile solvents such as toluene (MacIver, 2009), and that GABA plays an important role in neuronal development (Takesian et al, 2010), it is likely that this is an additional mechanism by which the abuse of inhalants can alter neuronal development and function.…”
Section: Methodsmentioning
confidence: 84%
“…The solvent‐induced reduction in brain weight and size is consistent with a previous study in which rat pups exposed to toluene between P4 and P10 displayed a dose‐dependent decrease in brain weight and astrocytic markers (Burry et al, 2003). Similarly, intraperitoneal toluene administration to rat pups at P4–P7 significantly reduced brain weight and caused glutamatergic dysfunction and neurobehavioral abnormalities (Chen et al, 2005; Chien et al, 2005). The data obtained in previous studies and in the present study are consistent with “fetal solvent syndrome”, which is found in human infants whose mothers were exposed to solvents during pregnancy.…”
Section: Methodsmentioning
confidence: 99%